A Parallel Connected Hybrid Microstrip-Substrate Integrated Waveguide Bandstop Filter - Guvenli, Kemal; Yenikaya, Sibel; Secmen, Mustafa (Elektronika ir Elektrotechnika, 2023)
This study presents an original parallel connected hybrid microstrip-substrate integrated waveguide (PCHM-SIW) bandstop filter. A low-pass filter implemented on a microstrip structure and a SIW-based high-pass filter are connected in parallel to each other. In this way, the aim is to obtain a bandstop filter in the novel hybrid design. The parallel connected hybrid microstrip-substrate integrated waveguide (PCHM-SIW) bandstop filter is synthesised, simulated, and produced. The effects of connecting filters in parallel are discussed. It is seen from the results of CST Studio Suite simulation that PCHM-SIW bandstop filter has a bandwidth of 2.85 GHz and a center frequency of 4.26 GHz. The frequency change rate of the center frequency between simulation and measurement is 7.02 % where it is just 3.76 % for the deviation in bandwidth. The results of the simulation and those of the measurement are close to each other. These results converge to ideal analytical results.